2011
DOI: 10.2174/157015911795596568
|View full text |Cite
|
Sign up to set email alerts
|

Human Endogenous Retroviruses in Multiple Sclerosis: Potential for Novel Neuro-Pharmacological Research

Abstract: There is growing evidence that the env genes of two or more human endogenous retroviruses (HERVs) of the W family are contributing to the inflammatory processes, and thus to the pathogenesis, of multiple sclerosis (MS). Increasing understanding of the human endogenous retroviral locus, ERVWE1, and the putative multiple sclerosis associated retrovirus, or MSRV, and in particular of the HERV-W env sequences associated with these, offers the potential of new lines of pharmacological research that might assist dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…This hypothesis opens the possibility of a co-contributing role or predisposing factors that will require additional studies on the HERV-W/MSRV brain proteomic profile in different ethnic populations [ 147 ]. In fact, considering the non-specific super-Ag activity of HERV-W/MSRV Env showed neuropathogenic effects coincident with the major hallmarks of MS inflammation [ 125 ], the HERV-W group could participate in a complex inflammatory interplay with other not fully understood factors, including genetic predisposition and exogenous infections [ 97 , 148 ]. It is noteworthy that a therapeutic treatment targeting HERV-W/MSRV has been proposed as a possible innovative approach for MS using the GNbAC1 monoclonal Ab developed to selectively recognize MSRV Env.…”
Section: Herv-w Expression In Ms and Other Autoimmune Diseasesmentioning
confidence: 99%
“…This hypothesis opens the possibility of a co-contributing role or predisposing factors that will require additional studies on the HERV-W/MSRV brain proteomic profile in different ethnic populations [ 147 ]. In fact, considering the non-specific super-Ag activity of HERV-W/MSRV Env showed neuropathogenic effects coincident with the major hallmarks of MS inflammation [ 125 ], the HERV-W group could participate in a complex inflammatory interplay with other not fully understood factors, including genetic predisposition and exogenous infections [ 97 , 148 ]. It is noteworthy that a therapeutic treatment targeting HERV-W/MSRV has been proposed as a possible innovative approach for MS using the GNbAC1 monoclonal Ab developed to selectively recognize MSRV Env.…”
Section: Herv-w Expression In Ms and Other Autoimmune Diseasesmentioning
confidence: 99%
“…As a member of the HERV‐W family, Multiple sclerosis‐associated retrovirus (MSRV) is replication competent and its sequences has been frequently found from MS patients . Although the complex inflammatory interplay with other factors is yet to be defined, MSRV Env gene has been suggested to play a role as a co‐factor in the immuno‐pathogenesis of Multiple Sclerosis either through inducing a potent inflammatory response or the gene itself is being induced by inflammatory factors . In response to certain inflammatory products or infectious agents, MSRV is also shown to encodes a protein that displays both inflammatory role .…”
Section: Introductionmentioning
confidence: 99%
“…45 Since then, research has been made on this field and it has been demonstrated that its presence is more frequent in MS patients than in controls. 46 Further, a replicationincompetent member of the HERV-W family was also found to be associated with MS. 47 So far, it is not entirely clear if the higher frequency of these retrovirus in MS patients has any pathogenic role or if it may only represent an irrelevant epiphenomenon.…”
Section: Gnbac1 (Anti-msrv-env)mentioning
confidence: 99%